CRAFTING BUSINESS MODEL INNOVATION AS THE ANCHOR STRATEGY TO SUSTAIN GREEN START-UP FIRM PERFORMANCE: A STUDY ON INDONESIA START-UP FIRMs - Batu, Kardison Lumban; Hasya, Afina (Master of Management, Faculty of Economics and Business, Diponegoro University, 2023)
This study is aiming at investigating the most suitable Business Model Innovation (BMI) for start-up firms during unpredictable market. The start-up firms are served as research population and sampling with various scope activities (trading, commerce, private sectors as well as limited) with employee size 10 until 40. 380 questionnaires were valid for further analysis gained from Google forms as well as questionnaires-based email. Structural Equation Modeling with AMOS 20 is used to analysis data. Current study proposed 10 hypotheses, 4 variables as the antecedents of BMI, and 2 mediating variables and green start-up performance (GSP) as the dependent variable. The Innovated Co-Creation Value (ICV) played a significant role as the key factor to increase the GSP. This is to mention that when a firm select and rely on the innovation and co-creation value during its operation, While the innovation to re-capture value during dynamic market, start-up firm experience high performance. To Support BMI, start-up firm is strongly suggested to build relationship with business partner and government. Business Relationship-Based (BRB) show a positive and significant impact on ICV & IRV. Aligned with Government Relationship-Based, it showed a significant impact on ICV & IRV. The finding also proved the significant impacts of Social Relationship-Based (SSB) on ICV & IRV. The three types of strategies proposed as the determinant factor of BMI is significantly accepted. For unusual finding, the networking capability which is designed and proposed as the key factor to enhance BMI is insignificant to both ICV & IRV.